The Legal Regime of Real Estate Investment Financing by Musharaka Contract - Morjane, Hicham (Université Hassan 1er, 2019)
Islamic banking is marked by its use of overly generous terms that are likely to apply to multiple factual situations forming more disputes than the law is supposed to settle, these terms are chosen in the style of Islamic Shariah and are considered as statements of Islamic principles rather than as the enactment of legal rules directly applicable to the facts and therefore able to propose solutions. Wishing to gain a better understanding of this young institution, the Musharakah contract in real estate financing. And as a result of our study and final arguments: this thesis will be a legal theory describing with legal simplicity the complex concept of the Musharakah contract in Islamic real estate financing in comparative law. In addition to the fact that the law must be normative, intelligible, in other words readable, clear and precise. Thus, our thesis is a research of analysis and demonstration, making the Musharakah contract in real estate financing go beyond the purely Islamic context and explicitly position it in a universal legal field as: "a legal regime of a contractual structure combining the company contract and the trust contract".
Keywords: Banque islamique; Financement immobilier; Investissement immobilier; Islamic banking; Moucharaka; Musharakah; Real estate financing; Real estate investments

The China-OHADA BIT, a step in the right direction : a new model of China-Africa BIT at a regional or sub-regional level - Sun, Sisi (Université de Montréal, 2019)
L’Afrique jouit non seulement de ressources naturelles, mais aussi d’un grand potentiel de marché. Ces dernières années, il y a une injection croissante d'investissements privés en provenance de Chine vers l’Afrique. La Chine souhaite exploiter le potentiel de l’Afrique en tant que marché émergent grâce aux investissements considérables réalisés par des entreprises privées. Parallèlement, les pays africains ont besoin d'investissements chinois dans divers domaines pour stimuler chaque aspect de leurs économies. L'investissement privé axé sur le marché nécessite un environnement d'investissement ouvert, stable, sécurisé et prévisible. Or, les traités bilatéraux d'investissement (TBI) existants entre la Chine et l'Afrique adoptent le modèle post-établissement axé sur la protection. La plupart de ces traités prévoient simplement des obligations générales de protection des investissements, laissant toutes les autres questions à la discrétion de l’État hôte. Les régimes juridiques instaurés par les TBI conclus entre la Chine et les États africains manquent de lisibilité, de prévisibilité et de cohérence. La conclusion de l'accord économique et commercial global entre l'UE et le Canada (AECG) suggère l’idée que la Chine pourrait s’inspirer de ce modèle pour conclure un accord bilatéral autonome avec les pays africains au niveau régional ou sous régional afin d’attirer des investissements chinois vers l’Afrique. Cet accord pourrait intervenir dans le cadre de l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) étant donné son niveau d’intégration et son autorité en matière de commerce et d’investissement sur le continent. Ce TBI modèle comportera des normes uniformes en matière d’accès aux marchés et de protection des investissements, ce qui limitera les risques d’interprétation divergente et partant, contribuera à l’instauration d’un climat d'investissement stable, sûr, prévisible et plus ouvert. Africa enjoys not only natural resources, but also market potential. There has been a growing injection of private investment inflows from China to Africa recently. China needs to exploit Africa’s potential as an emerging market for its tremendous investments by private enterprises. Moreover, the African countries need Chinese investments in various areas to boost aspects of their economies. Private, market-oriented investment calls for an open, stable, secure and predicable investment environment. However, existing bilateral investment treaties (BIT) between China and Africa adopt the protection-oriented, post-establishment model. The treaties merely provide for some general obligations of investment protection, leaving all other matters to the policy discretion of the host state. The China-Africa BIT regime is sporadic, uninformed and incoherent. The conclusion of the Comprehensive Economic and Trade Agreement between the EU and Canada (CETA) develops the idea that China might conclude a standalone BIT with the African countries at a regional or sub-regional level to attract Chinese investment inflows into Africa through an open, coherent and uniformed investment scheme. Given the integration of Organisation pour l’harmonisation en Afrique du droit des affaires (OHADA) to be one single jurisdiction over trade and investment, the China-OHADA BIT is the one most likely to be expected. This standalone BIT regime inherently calls for an absolute standard for market access and investment protection, and uniformity to limit the discretion of interpretation, and as such, contribute to a more open, stable, secure and predictable investment climate.
Keywords: BIT regime; China-OHADA BIT; Chine-OHADA TBI; Climat d'investissement; Discrétion politique; Investment climate; Investments; Policy discretion; TBI modèle

Le défi de l'Organisation pour l'harmonisation en Afrique du droit des affaires face au développement des marchés financiers africains: Quid de la protection des investisseurs - Sita, Gloria Lubaki (Recht in Afrika, 2019)
By the time the founding fathers of the Organization for the Harmonization of Business Law in Africa (OHADA) signed the Treaty of Port Louis, the financial markets in Western and Central Africa were embryonic. Nowadays the situation has changed and it seems appropriate to reconsider relationship between OHADA law and securities exchange markets. Indeed, OHADA's Community legislation has to deal with the securities markets covered and serve both the proper functioning of the market and the protection of investors. The uniform Act on Commercial Companies and Economic Interest Groupings contains provisions referring to specific financial rules. However, is this sufficient to earn the public trust? Financial market law is a complex discipline. If we supplement this the effort required for investors to find their way between the West African Economic and Monetary Union (WAEMU) or the Economic and Monetary Community of Central Africa (CEMAC) stock exchange law and national constraints throughout OHADA, the following question must be asked: How is the investor's interest protected in this legal jungle? This paper tries to analyse the legal mechanisms of investor protection in the WAEMU Regional Stock Exchange and the Central African Stock Exchange, combining them with the uniform law for commercial companies of OHADA.